2019
DOI: 10.1177/0264619619883900
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept of adolescents with visual impairments

Abstract: An account is given of a current research project which is examining the impact of social inclusion on the self-concept of adolescents with visual impairments and the way this differs from their typically developing sighted peers. The study considers developmental and cognitive theories which are used to explain the development of self-concept in typical and atypical adolescents and the impact of social inclusion on this particular aspect of mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…El autoconcepto se refiere al conjunto de características que cada persona utiliza para definirse como individuo y diferenciarse de los demás (Harter, 1999), estando integrado por: la percepción que una persona tiene de sí misma (autoconcepto propiamente dicho o autoimagen); el valor que atribuye a su particular manera de percibirse (la autoestima); y su comportamiento, ya que el autoconcepto influye en la conducta y la condiciona en gran medida. Asimismo, tiene un carácter jerárquico y multidimensional (González-Pienda et al, 2003) y evoluciona con los años como resultado de la influencia sociocultural, educativa y experiencia personal en su medio social (Manitsa, Barlow-Brown y Lyons, 2019), aceptándose que mientras el autoconcepto general puede mantenerse prácticamente inalterable (Coll, 2002), los más específicos pueden variar.…”
Section: Introductionunclassified
“…El autoconcepto se refiere al conjunto de características que cada persona utiliza para definirse como individuo y diferenciarse de los demás (Harter, 1999), estando integrado por: la percepción que una persona tiene de sí misma (autoconcepto propiamente dicho o autoimagen); el valor que atribuye a su particular manera de percibirse (la autoestima); y su comportamiento, ya que el autoconcepto influye en la conducta y la condiciona en gran medida. Asimismo, tiene un carácter jerárquico y multidimensional (González-Pienda et al, 2003) y evoluciona con los años como resultado de la influencia sociocultural, educativa y experiencia personal en su medio social (Manitsa, Barlow-Brown y Lyons, 2019), aceptándose que mientras el autoconcepto general puede mantenerse prácticamente inalterable (Coll, 2002), los más específicos pueden variar.…”
Section: Introductionunclassified
“…Two quantitative studies do consider students’ perspectives, one comparing the physical activities (Giese et al, 2017), the other comparing bullying between students with and without VI (Pinquart & Pfeiffer, 2011). There are also international studies on the well-being and social participation of students with VI (de Verdier, 2016; Jessup et al, 2018; Lourens & Swartz, 2016; Manitsa et al, 2019; Tanure Alves et al, 2018), some of which conducted qualitative interviews with the students. Main results concluded that students with additional disabilities are less socially integrated than those who are partially sighted.…”
mentioning
confidence: 99%